Chronic Stress Decreases Cerebrovascular Responses During Rat Hindlimb Electrical Stimulation - Lee, Sohee; Kang, Bok-Man; Shin, Min-Kyoo; Min, Jiwoong; Heo, Chaejeong; Lee, Yubu; Baeg, Eunha; Suh, Minah (Frontiers in Neuroscience, 2015)
Repeated stress is one of the major risk factors for cerebrovascular disease, including stroke and vascular dementia. However, the functional alterations in the cerebral hemodynamic response induced by chronic stress have not been clarified. Here, we investigated the in vivo cerebral hemodynamic changes and accompanying cellular and molecular changes in chronically stressed rats. After three weeks of restraint stress, the elicitation of stress was verified by behavioral despair in the forced swimming test and by physical indicators of stress. The evoked changes in the cerebral blood volume and pial artery responses following hindpaw electrical stimulation were measured using optical intrinsic signal imaging. We observed that, compared to the control group, animals under chronic restraint stress exhibited a decreased hemodynamic response, with a smaller pial arterial dilation in the somatosensory cortex during hindpaw electrical stimulation. The effect of chronic restraint stress on vasomodulator enzymes, including neuronal nitric oxide synthase (nNOS) and heme oxygenase-2 (HO-2), was assessed in the somatosensory cortex. Chronic restraint stress downregulated nNOS and HO-2 compared to the control group. In addition, we examined the subtypes of cells that can explain the environmental changes due to the decreased vasomodulators. The expression of parvalbumin in GABAergic interneurons and glutamate receptor-1 in neurons were decreased, whereas the microglial activation was increased. Our results suggest that the chronic stress-induced alterations in cerebral vascular function and the modulations of the cellular expression in the neuro-vasomodulatory system may be crucial contributing factors in the development of various vascular-induced conditions in the brain.